2008
DOI: 10.1080/00365540801898598
|View full text |Cite
|
Sign up to set email alerts
|

HIV seroprevalence among new TB patients in the civilian and prisoner populations of Donetsk Oblast, Ukraine

Abstract: After the Russian Federation, Ukraine is the country of the Former Soviet Union experiencing the greatest epidemics of tuberculosis (TB) and HIV, although complete official data are not available. This study investigates the prevalence of HIV among new TB patients in the civilian and penitentiary populations of Donetsk Oblast. A cross-sectional survey was undertaken of 1507 new patients with TB (1351 civilians, 156 prisoners) between January and June 2006. The prevalence of HIV among patients with TB was 15.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Only six of the studies retrieved [2,50,53,62,69,70] provided any comparison of a prisoner's risk of co-infection to that of the general population. All of these studies found the risk or prevalence of co-infection to be greater among prison residents than that of the general community.…”
Section: Resultsmentioning
confidence: 99%
“…Only six of the studies retrieved [2,50,53,62,69,70] provided any comparison of a prisoner's risk of co-infection to that of the general population. All of these studies found the risk or prevalence of co-infection to be greater among prison residents than that of the general community.…”
Section: Resultsmentioning
confidence: 99%
“…HIVinfected persons in congregate settings, such as prisons and centers for refugees or internally displaced persons, have a higher risk and incidence of TB, HIV infection, and drug use in many countries [53][54][55]. There is often increased transmission of HIV and TB, including MDR-TB, in prisons [51,54,56]. The crowded living conditions in most congregate settings facilitate the transmission of TB.…”
Section: Hiv Infection-related Tb In Special Populationsmentioning
confidence: 96%
“…This further compounds the impact of HIV infection-related TB in drug users who are either HIV infected or vulnerable to HIV infection. Access to effective interventions for HIV-infected patients with TB who are also drug users is worsened by poor treatment access, low rates of TB treatment completion, and exposure to prison settings [51]. Early introduction of harm-reduction measures in Australia and New Zealand led to a rate of HIV infection of 1.5% among drug users, and in eastern Europe, South Asia, and Latin America, rates are upward of 40% [49].…”
Section: Hiv Infection-related Tb In Special Populationsmentioning
confidence: 98%
“…Eastern Europe (EE) presents major challenges in terms of management of the Tuberculosis (TB)/HIV epidemic, mainly due to the high rates of multi-drug resistant (MDR) TB. [1][2][3] The numbers of TB/HIV coinfected people are rapidly increasing, and mortality of TB/HIV patients in this region remains among the highest in the world 2,[4][5][6][7] , there is very little published evidence from EE on management of coinfected patients and risk factors for excess mortality. We have previously described the clinical aspects of TB/HIV epidemic in EE, when the retrospective TB:HIV study was conducted.…”
Section: Introductionmentioning
confidence: 99%